Effect of modified cassava starch in reduced-fat mayonnaise by correlating emulsion stability with anti-oxidation reaction using gas chromatography-mass spectrometry (GC-MS) - Parreño, Ronaldo P. Jr; Carandang, Maricar B. (Vol. 150, No. 4 (August 2021) pages 753-763.)
"Modified starches are essential firming additives in many food processes as they act as emulsion stabilizers. Presently, they are produced mostly from corn and potatoes, but cassava is a good alternative source to augment the rising global demand for starch. In this work, cassava starch from a native variety called Manihot esculenta Crantz, modified by facile heat-moisture treatment (HMT) method was used in reduced-fat mayonnaise to retain product consistency and texture but, more importantly, to contribute to the stabilizing effect of emulsions. Varying amounts of modified cassava starch in mayonnaise formulation were evaluated to correlate emulsion stability with a reduction in the amount of oil and the presence of anti-oxidation compounds that slow down chemical processes"-Title page.